Influence of Negative Affect, Self Efficacy, Frugality Injunctive Norm on Consumer Guilt and its Implications on Consumer Price Consciousness in e-Commerce - Azzahra, Saffa (Student Journal of Business and Management, 2024)
The purpose of this study was to determine the effect of negative affect, self efficacy, frugality injunctive norm on consumer guilt and its implications for consumer price consciousness in e-commerce. The sampling technique in this study used a non-probability sampling technique and data collection was carried out by distributing online questionnaires to respondesnts. The number of samples was 200 copies, but only 190 copies could be tested. The data analysis technique used Structural Equation Modelling (SEM) using the PLS program. Hypothesis testing using the bootstrapping method. The results of this studi indicate that negative affect has a significant positive effect on consumer guilt. Self efficacy has a negative relationtship that is not proven to have a significant effect on consumer guilt. Frugality injunctive norm has a significant positive effect on soncumer guilt. Consumer guilt is proven to have an effect on consumer price consciousness.